The Effect of Parents’ Parenting Style on the Fourth-Grade Natural Science Students’ Learning Motivation at Elementary School - Harniwati Halawa; Bogor Lumbanraja; Patri Janson Silaban; Dewi Anzelina; Anton Sitepu (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper explains the effect of parents’ parenting styles on students’ learning motivation in natural science subjects. The study was conducted in class IV at SD Negeri 060938 Medan Johor using an associative quantitative research method. The population consisted of 36 fourth-grade students, and total (saturated) sampling was applied. The results show that the correlation coefficient obtained was rcount = 0.97, which is greater than rtable = 0.329, indicating that the alternative hypothesis (Ha) is accepted. This means there is a significant effect of parents’ parenting styles on students’ learning motivation. The t-test results also support this finding, with tcount = 25.73 exceeding ttable = 2.030, confirming that Ha is accepted. Overall, the findings demonstrate a positive and significant effect of parents’ parenting styles on the learning motivation of fourth-grade students in natural science subjects at SD Negeri 060938 Medan Johor in the academic year 2022/2023.